Kaitiakitanga – principles for protecting and promoting tamariki and rangatahi wellbeing in Growing Up in New Zealand. Issue 3 (27th May 2022) - Paine, Sarah-Jane; Neumann, Denise; Langridge, Fiona; Peters, Aysha; Kingi, Te Kani
ABSTRACT: Growing Up in New Zealand (GUiNZ) is the largest contemporary longitudinal study of child development in Aotearoa New Zealand. The aim of the study was to recruit a large, socioeconomically and ethnically diverse cohort of children, with successful recruitment of 1246 pregnant Māori women. This paper describes the development and operationalisation of the GUiNZ Kaitiaki principles which provide a framework for ensuring that Māori rights and aspirations for research and policy development are upheld as part of the study. We also consider how the Kaitiaki principles might inform the next phase of GUiNZ, particularly with respect to the potential guardianship role that rangatahi (young people) should have as their contribution to the study expands. Finally, this commentary seeks to highlight the significant opportunities that Māori values and philosophies bring to longitudinal research in Aotearoa including through strengthening our connections with whānau and Maori communities.